Learning from mistakes I: why it is important. (2nd July 2019) - Ellis, Peter; Abbott, Jane
Abstract : In this article, Peter Ellis and Jane Abbott discuss what mistakes in healthcare might look like, and why it is so important that we learn from them when they do occur